ATTRIBUTIVE PROPAEDEUTICS OF ACCOUNTING REPORTING AS A MEANS OF COMMUNICATING THE SYSTEM OF INDICATORS IN DESCRIPTIVE MODELS OF ECONOMIC ANALYTICS - Golovko V. I.; Sharmanska V. M.; Tsybulnyk M. O. (World Science, 2018)
The article deals with accounting reporting as a means of communicating the system of indicators in descriptive models of economic analytics. Formalized algorithmic procedures for calculating key invariant indices suitable for use of standard packets of analytical orientation applications are constructed. The descriptive model and the formation of its information support are considered. In forming the system of indicators for conducting an economic analysis of the financial condition of the enterprise, in order to reduce the number of calculations and improve the efficiency when conducting an express analysis of the financial condition of the enterprise, a heuristic method of permissible multicollinearity with acceptable (tested by practice) characteristics is proposed.